Shaping the competencies of the future: the importance of developing soft skills in higher education within the landscape of information technologies - Burda, Yu.; Samus, Т.; Bazhmina, E.; Bondarenko, O.; Myrnyi, D. P.; Мирний, Дмитро Петрович (My University, 2024)
Abstract: The article emphasizes that modern professional activity requires mastery of not only highly specialized knowledge but also soft skills. The peculiarities of modern society, which has passed from the VUCA state to the BANI state, are noted, emphasizing that it implies even greater turbulence and unpredictability of the environment, as well as the ever-growing role of information technologies. Today, in the labor market, “soft” skills play a key role in professional activity. Therefore, the task of higher education is to educate a professional who can realize himself in the conditions of high competition, which requires the introduction of educational technologies that form in students' soft skills with solid digital components. The article is devoted to soft skills, which are necessary for young specialists starting a professional career. The objectives of the study were: to determine the optimal composition of soft skills, most in-demand among employers; to evaluate their importance for the successful start of the professional career of young engineers; to reveal the main problems of the formation of soft skills within the educational process. Formulated conclusions can be used to improve university training of young specialists competent in the labor market in the BANI-environment.
Keywords: soft skills; university; VUCA; BANI; experimental learning; information technologies